THE EFFECT OF FRICTION TIME VARIATIONS ON DISSIMILAR MATERIAL WELDING JOINTS AND HARDNESS VALUE USING A BAR-PLATE ROTARY FRICTION WELDING MACHINE - Sinabutar, Jimmi pranata; Yohanes (Journal of Renewable Energy and Mechanics, 2024)
This research aims to determine the effect of variations in friction time on welded joints of dissimilar materials and hardness values. The method used is the friction welding method. One of the materials widely used in industrial products is mild steel AISI 1037 and stainless steel 304. One of the tools used is a bar-plate upright rotary friction welding machine. The parameters used are friction time variations of 25-35 seconds, 55-65 seconds and 115-125 seconds with a rotational speed of 2,484 rpm, friction pressure of 0.5 MPa, forging pressure of 0.7 MPa, forging time of 10 seconds. From the results of the connection several tests were carried out, namely liquid penetrant , macro observation and hardness test. The results of liquid penetrant testing and macro observations showed no influence on the welding area. The results of hardness testing have an influence on the hardness value. In the interface area, the friction time variation of 120 seconds has the highest hardness value of 161.67 VHN. The lowest hardness value in the interface area with a friction time variation of 30 seconds is 152.90 VHN. Where the longer the friction time, the hardness value also increases.